The power of gold: a tip for an uncrossable ostial lesion - K. Ściborski, Krzysztof; Furdal, Michał; Porada, Adam; Szymkiewicz, Paweł; Telichowski, Artur (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Uncrossable lesions are lesions that cannot be crossed with a balloon or microcatheter after guide wire crossing. They constitute a considerable challenge in coronary interventions and are associated with poor outcome in patients undergoing rotational atherectomy (RA) [1]. Most of the documented methods cannot be applied in true aorto-ostial lesions with severe stenosis. Such lesions require a nonstandard approach that has not been precisely described in any expert documents so far [2–4].